Kritik Nalar Feminisme Dalam Aturan Kuota Perempuan Di Ruang Politik - Ahmad Khoirul Fata (Puslatbang KHAN, 2014)
Quota of 30 percent for women in the central board of political parties and the list of candidates are believed to be effective tool to increase the number of women representation in parliament. In the end, women will have a significant role in the policy-making process. But these rules have a number of problems related to basic assumptions about gender justice. Quota for women implicitly looks woman homogeneously, ignore the personal factor, specific and unique conditions surrounding women. Ignorance of the things that the typical course of a condition not fair to women who may have negative consequences for women themselves and the people they represent. This paper attempts to unravel the problem of justice contained in the rules of the quota of women representation in the parliament and central board of political parties.